Pertukaran Data Pada Rumah Sakit Di Makassar Berbasis Xml Based - andi ikmal rachman; Luqman Fanani Mz; Agus Halid; Suriansyah B; Gita Pratiwi (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
Data exchange in hospitals plays an important role in hospital information systems. The problem then arises when there are different systems in two places that want to be connected. The technology used must sacrifice business, cost and development, now a method of interoperability with XML (eXtensible Markup Language) has been proposed. This method can be applied in many distributed computing technologies and problems, especially for data exchange with different platforms. XML-based data exchange is becoming one of the standards in developing frameworks for information systems. This is done to find out whether the programming algorithms used in each program in the system are correct or there are still errors, besides that, what is even more important is whether the system built can meet its objectives. From the design process that has been carried out, it can be concluded that a method can be built that uses a data exchange system between two systems by utilizing XML Based data computing. The data must be easily understood by both parties so as not to cause communication errors so that when the system process can run smoothly.